FishMap Zv8 update—a genomic regulatory map of zebrafish - Bhartiya, D; Maini, J; Sharma, M; Joshi, P; Laddha, S; Jalali, S; Patowary, A; Purkanti, R; Lalwani, M; Singh, A; Chauhan, R; Singh, N; et al. (Mary Ann Liebert, Inc. publishers, 2010)
The advancements in genomics technologies and the amenability to large-scale computational analysis have contributed immensely to the understanding of the zebrafish genome, its organization, and its functional correlates. Translating genomics information into biological meaning would require integration and amenability of data and tools. FishMap is a community resource for genomic datasets on zebrafish created with a vision to provide relevant and readily available information to zebrafish researchers. The present update of FishMap has kept up with the availability of the latest zebrafish genome assembly (Zv8). In this update, particular emphasis has been given to noncoding RNAs and noncoding RNA-mediated regulation in addition to genomic regulatory motifs, which are emerging areas of vertebrate biology. FishMap Zv8 update also features a sequence mapping and analysis server. Consistent with its commitment to make the information freely available to the community, FishMap features options to share data between compatible resources in addition to making it amenable to programmatic access. FishMap Zv8 update is available at http://fishmap2.igib.res.in.